2018
DOI: 10.1016/j.neulet.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine modulates aggressive behavior in adult zebrafish

Abstract: Ketamine is a non-competitive glutamatergic antagonist that induces analgesia and anesthesia. Although ketamine displays anxiolytic and antidepressant properties, it may induce pro-psychosis and hallucinogen effects, as well as stereotypic behaviors following acute administration at sub-anesthetic doses. Since heightened aggression is maladaptive and may comorbid with various neuropsychiatric disorders, we aimed to investigate whether ketamine modulates aggressive behavior in adult zebrafish. Fish were acutely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 37 publications
1
19
1
Order By: Relevance
“…Interestingly, pharmacological studies revealed high correlation with regard to the ability of larval and adult zebrafish to mimic positive SCZ symptoms. For example, ketamine [65,66] and MK-801 (also called dizocilpine) [54, 67] induce a robust increase in locomotion. Moreover, d-amphetamine or D 2 receptor agonists elicit the same locomotor response in adult zebrafish [68,69] as in rodents [70][71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pharmacological studies revealed high correlation with regard to the ability of larval and adult zebrafish to mimic positive SCZ symptoms. For example, ketamine [65,66] and MK-801 (also called dizocilpine) [54, 67] induce a robust increase in locomotion. Moreover, d-amphetamine or D 2 receptor agonists elicit the same locomotor response in adult zebrafish [68,69] as in rodents [70][71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are lack of studies about anti-aggressive effect of ketamine to rodent. Recently, one study reported lower sub-anesthetic concentrations (2 mg/L) increase aggression towards mirror, higher ketamine concentrations (20 mg/L and 40 mg/L) elicit stereotypic behaviors and reduce aggression for adult zebrafish [3]. Another study showed acute ketamine (7.5 and 10.0 mg/kg) suppressed aggressive performance in both control group and in historically alcohol-treated group of adult mice (PND 8 weeks) [26].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have assessed the therapeutic effects of ketamine, demonstrating its antidepressant and anxiolytic effects in humans as well as in rodents [2]. However, there are lack of studies about therapeutic effects of ketamine on aggression [3].…”
Section: Introductionmentioning
confidence: 99%
“…Drug-induced stereotypic behaviors are not well characterized in zebrafish, but some authors suggest they may be displayed as altered rotation movements (Michelotti et al, 2018). To date, only a few studies explored the effects of MK-801 on stereotypy-related behaviors in zebrafish, and there is no study with AMPH.…”
Section: Discussionmentioning
confidence: 99%